REGULATION OF OFFENCES AGAINST PUBLIC SECURITY IN THE CRIMINAL CODE OF ROMANIA - Iancu, Elena-Ana (International Journal of Legal and Social Order, 2021)
The aim of this article is to highlight the place the Romanian lawmaker has given to criminal offences against public security in the criminal law. At the same time, we seek to delineate the legal object of crimes against public security from that of crimes that affect relations of social coexistence, especially those protecting public order and peace. Knowledge of the legal object contributes to a better understanding of the concepts of public security and social order that are interdependent with law and human capital. Also, through the method of documentation we aimed to highlight, in the context of the pandemic: some legislative changes that had an impact on the activities carried out in the field of public security; the main measures taken to ensure the safety of the person and the observance of health measures in criminal proceedings; the activities that were carried out online in the judicial proceedings and the manner in which the intra-institutional communication or inter-institutional communication took place; the main changes brought by the legislator in the matter of criminal offences against public security (safety).